Love-Based Curriculum for Humanistic Islamic Religious Education Learning at Al-Azhar Medan Elementary School - Himan Rizky Hasibuan; Hasan Basri (Journal of Contemporary Islamic Primary Education, 2026)
This study aims to examine in-depth the implementation of a love-based curriculum in Islamic Religious Education (IS) and analyze its implications for the development of humanistic character in students at Al Azhar Model Elementary School, Medan. This study uses a qualitative approach with field research. Data collection was conducted through participant observation, in-depth interviews with two Islamic Education teachers, and documentation studies. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The research results show that the implementation of a love-based curriculum is reflected in learning practices that place the value of compassion as the primary foundation of educational interactions, manifested through teacher role models, empathetic communication, and respect for the diversity of student characters. Teachers serve not only as learning facilitators but also as mentors who guide students' ongoing emotional and spiritual development. Therefore, these findings indicate that this approach contributes to creating a more inclusive and conducive learning atmosphere, increasing students' active participation, and fostering attitudes of empathy, tolerance, and social responsibility.